Some Cambridge controversies in the theory of capital - Harcourt, G. C. (Geoffrey Colin), 1931-; Cohen, Avi J.; Mata, Tiago (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
The Cambridge Capital Controversy was one of the most significant debates in Twentieth Century economics. First published in 1972, this book provides an accessible reconstruction of the controversy with detailed discussion of the major points raised by its primary protagonists: Piero Sraffa and Joan Robinson on the post-Keynesian side (Cambridge, UK) and Robert Solow and Paul Samuelson on the neo-classical side (Cambridge, MA). The book is now considered to be a classic. This fiftieth anniversary edition comes with a new preface by the author and two new afterwords that reflect on the author's contribution to the field and the significance of the book in the history of economics. Topics covered include the measurement of capital, the revival of interest in Irving Fisher's rate of return on investment, the double-switching debate, Sraffa's prelude to a critique of neoclassical theory, and the 'new' theories of the rate of profits in capitalist society.
Title from publisher's bibliographic system (viewed on 10 Jun 2022).
Keywords: Capital; Capital -- Mathematical models